Antifungal metabolites, their novel sources, and targets to combat drug resistance - Choudhary, Megha; Kumar, Vijay; Naik, Bindu; Verma, Ankit; Saris, Per Erik Joakim; Kumar, Vivek; Gupta, Sanjay (Frontiers in Microbiology, 2022)
Excessive antibiotic prescriptions as well as their misuse in agriculture are the main causes of antimicrobial resistance which poses a growing threat to public health. It necessitates the search for novel chemicals to combat drug resistance. Since ancient times, naturally occurring medicines have been employed and the enormous variety of bioactive chemicals found in nature has long served as an inspiration for researchers looking for possible therapeutics. Secondary metabolites from microorganisms, particularly those from actinomycetes, have made it incredibly easy to find new molecules. Different actinomycetes species account for more than 70% of naturally generated antibiotics currently used in medicine, and they also produce a variety of secondary metabolites, including pigments, enzymes, and anti-inflammatory compounds. They continue to be a crucial source of fresh chemical diversity and a crucial component of drug discovery. This review summarizes some uncommon sources of antifungal metabolites and highlights the importance of further research on these unusual habitats as a source of novel antimicrobial molecules.